TANTANGAN DAN PELUANG PENDIDIKAN ISLAM DI PESANTREN PADA ERA DISRUPSI - Khotimah Suryani (Journal Multicultural of Islamic Education, 2022)
General Education is considered to have not been able to equip its graduates to avoid immoral behavior. The importance of the internalization of values ​​in an education. Islamic boarding schools are one of the educational institutions that are able to internalize the values ​​of Islamic teachings as provisions in the formation of the nation's personality. The younger generation who have superior personalities can avoid immoral behavior. The phenomenological approach in this study is aimed at portraying the existence of disruption as a phenomenon associated with Islamic boarding schools, from the point of view of thoughts, perceptions, and beliefs attached to the subject. Through reflective logic, the empirical evidence of Islamic boarding schools is abstracted rationally in the logic of induction and described in a systemic-comprehensive manner in the logic of deduction. Steps to renew pesantren can be done by granting formal legality in the form of diplomas, adjusting the curriculum by adding compulsory subjects, and expertise training programs. Islamic boarding schools as a miniature of society have a role in creating the unity and stability of community harmony. Islam Nusantara as a product of Islamic boarding schools has been able to stem the disruption of Islamic religious traditions. The concept of Tabarukkan and simplicity in Islamic boarding schools can produce young generations who are resilient in dealing with difficult problems in the era of disruption.